INTERAKSI SOSIAL DAN TINGKAT PENDAPATAN NELAYAN PURSE SEINE DI DESA LATUHALAT KECAMATAN NUSANIWE KOTA AMBON - Costansa Glory Lessil; Costantinus Sahanaya (Universitas Pattimura, 2025)
This study was conducted to describe the forms of social interaction that develop within fishing activities and to analyze the income levels earned by fishermen at the business, owner, and crew levels. A descriptive method was employed, using a qualitative approach to examine social interaction patterns and a quantitative approach to calculate income based on cost structure, profit-sharing mechanisms, and production fluctuations between the fishing season and the less productive season. The research involved 5 Purse Seine unit owners out of a total of 10 units, as well as 25 crew members working on those five units. The results indicate that social interaction among Purse Seine fishermen in Latuhalat Village consists of three main forms: cooperation, competition, and conflict. Cooperation is reflected in the relationships between boat owners and crew members, among the crew themselves, and between fishermen and fish collectors (jibu-jibu) as well as transport drivers. Cooperation among fishing groups also emerges through mutual assistance in providing equipment or operational needs. Competition arises both among individuals and between fishing units in their efforts to obtain larger catches, while conflict is typically triggered by misunderstandings or unequal distribution of income. Economically, fishermen’s business income shows significant variation between seasons. During the fishing season, the average business income reaches IDR 6,086,651 per trip, with owners and crew members each receiving IDR 2,434,661, and rumpon income amounting to IDR 1,217,330. In contrast, during the less productive season, average business income decreases to IDR 1,392,251 per trip. These findings highlight that social interactions and seasonal fluctuations strongly influence the economic stability of purse seine fishermen’s households in Latuhalat Village.